Saving energy and improving performance in SDN using rate adaptation technique - Rout, Suchismita; Sekhar Patra, Sudhansu; Bibhudatta, Sahoo (International Journal of Engineering and Technology, 2018)
Energy efficiency in wired networks has received considerable attention over the past few years for its heavy economic impact. Energy consumption in such network is becoming a challenging issue. Among all these wired networks Software Defined Networking (SDN) is considered as an intelligent network in which use of programmability provides the best solution for network operation. The logical separation of data plane and control plane enhances its network functionality. Despite of all these mechanisms, energy consumption is also an alarming issue in SDN. Various researchers propose many approaches in order to utilize the energy in its best way. Herein we consider the normal scenario of a data center network, and propose a new energy efficient routing algorithms to improve the performance in SDN, called SERAT. In this work, we focus on discrete of data rate of the link in order to minimize energy consumption in the network. In wired network the underutilized links are even operated in high data rate, increasing energy consumption. In order to reduce energy consumption of the network the links must be operated as per their utilization factor. We have used an output buffer queue with two levels of threshold values in order to monitor the performance of the network. Simulation result shows that the proposed technique leads to major amount of energy savings without mush affecting the throughput.